2022
DOI: 10.1088/1755-1315/1079/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study of Hydraulic Vibration caused by Clearance Flow in a Pump Turbine

Abstract: The pumped-storage power station needs to adjust the load to meet the needs of the power grid at any time and cannot always operate under the best working conditions. In practical operation, vibration phenomenon with complex inducements occasionally occurs. In the stable operation of the Baishan energy storage power station, the headcover vibrates obviously. To find the cause of vibration, this paper modeled the unit flow area, used the numerical simulation method for steady and unsteady calculation, extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The total number of mesh nodes was 2.6 million, and the number of mesh nodes per component is shown in Table 2. Based on the grid independence verification performed in the authors' previous study [7], this grid density is sufficient to resolve the internal flow patterns within the runner and draft tube. Numerical simulations were carried out in ANSYS CFX using the Reynolds averaged Navier-Stokes (RANS) equations [31] for the internal flow characteristics of the pump turbine.…”
Section: Research Object and Numerical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total number of mesh nodes was 2.6 million, and the number of mesh nodes per component is shown in Table 2. Based on the grid independence verification performed in the authors' previous study [7], this grid density is sufficient to resolve the internal flow patterns within the runner and draft tube. Numerical simulations were carried out in ANSYS CFX using the Reynolds averaged Navier-Stokes (RANS) equations [31] for the internal flow characteristics of the pump turbine.…”
Section: Research Object and Numerical Methodsmentioning
confidence: 99%
“…The numerical study by Zhu et al [6] indicated that the intense pressure fluctuation is related to the non-uniform distribution of vortex structures in the vaneless space. The simulation results by Hu et al [7] found triangular or quadrilateral flow patterns in the upper crown cavity, which is an important reason for the low-frequency components in this region. Asomani et al [8] reviewed the influence of design parameters on the internal flow characteristics of pump turbines, and the main influence of geometric parameters is the RSI characteristics of different units.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, after the guide vane opening, 7 fn and 21 fn appear at the elbow, which are almost non-existent before the guide vane opening, indicating that the increase in discharge enhances the influence of the runner blades on the upstream. The author's previous numerical study also mentioned that in the No-discharge Condition of the pump mode, the relative velocity between the runner and the fluid inside the runner is very low, and the water body and blades rotate as a whole rigid body, with only the fluid migration at the runner edge being evident [31]. In addition, after the guide vane opening, 2 fn and the frequency band centered at 1.5 fn are significantly enhanced, with the center frequency of the 1.5 fn band being slightly lower than that before the guide vane opening.…”
Section: Pressure Fluctuationmentioning
confidence: 99%
“…The problems of abnormal head-cover vibration also occurred in some other pumped storage power plants both domestically and internationally [5][6][7] , and most of the treatment schemes require the generator-turbine unit to be dismantled and renovated (A grade unit overhaul), which requires 4 to 5 million RMB in labor costs, about 100 days of working time, and corresponding management costs; the commissioning time of the pumped storage power plant or the unit equivalent availability factor will be seriously influenced. To permanently solve the abnormal head-cover vibration problem, the modifications of the runner structure or head-cover structure are necessary, however, this is a costly solution.…”
mentioning
confidence: 99%